Compilación bibliográfica en Iberoamérica desde el 2005 al 2020 sobre competencias y estrategias que mejoren la comunicación asertiva y la convivencia escolar, frente al bullying verbal. (2021)
Bullying is a problem that has spread throughout the country and mainly affects the contexts of the educational community, families, school, students, neighborhoods and other actors. In fact, different investigations highlight that one of the types of bullying that most affects school contexts is verbal bullying, which is based on attacking, intimidating or discriminating against others with the use of inappropriate words